Global Supply Chain Management: Trends, Challenges, and Strategies - Sujatmiko, Sujatmiko; Krisnanto, Budhi; Sasmita, Halida; Wahab, Abdul (Yayasan Vifada Cendikia Indonesia, 2024)
This comprehensive study delves into the intricate dynamics of global supply chain management, aiming to uncover prevailing trends, challenges, and strategies embraced by organizations. Through meticulous examination of qualitative and quantitative data, the research builds upon previous works by Christopher (2016), Ferdows et al. (2017), and Pagell and Shevchenko (2014), emphasizing the impact of market fluctuations, technological innovations, and sustainability principles. The study reveals the accelerating adoption of technologies like blockchain, IoT, and AI, reshaping traditional supply chain processes and driving operational efficiency. Despite technological advancements, organizations face challenges including market volatility, supplier reliability, logistical complexities, and sustainability imperatives. To address these challenges, collaborative approaches and sustainability integration emerge as crucial strategies, echoing findings from Mentzer et al. (2018) and Gold et al. (2010). The implications highlight the necessity for organizations to adapt to technological advancements, foster collaboration, and integrate sustainability into supply chain strategies to navigate complexities and foster resilience in the global market.